RETRACTED: The Evaluation of Final Assignment System Using the USE Questionnaire Approach - Purwinarko, Aji; Subagja, Mona; Yanuarto, Alfath (Universitas Negeri Semarang, 2021)
This paper is retracted by editor due to publication ethics missconducted by author (simultaneously publication in other issue).Similar article has appeared inÂ https://journal.unnes.ac.id/nju/index.php/sji/article/view/26053